Cytomegalovirus infection and Guillain-Barré syndrome: A first case-control study in children in Iran - Mamishi, Setareh; Ashrafi, Mahmoud Reza; Mohammadi, Mahmoud; Ghaletaki, Gholamreza Zamani; Aziz-Ahari, Solmaz; Mahmoudi, Shima (Iranian Journal of Child Neurology, 2021)
Objective: Guillain-Barré syndrome (GBS) is an immune-mediated disease of the peripheral nervous system which affects all age groups through the world. Although the pathogenesis and optimal treatment of GBS are still not completely established, one of the most common infectious diseases to trigger the syndrome is cytomegalovirus (CMV) infection. GBS following CMV infections is rarely reported in childhood and there is no data on GBS with antecedent CMV infection in children in Iran. The aim of this study was to evaluate the association of CMV infection and GBS in children in Iran. Materials & Methods: Case-control study design was used in 30 cases of Guillain-Barre syndrome, and 30 matched controls. All serum samples were tested for the presence of anti-CMV IgM and IgG antibodies using a commercially available ELISA (EUROIMMUN Medizinische, Germany).CMV viral DNA in the specimen was detected using polymerase chain reaction (PCR), (Cytomegalovirus PCR Detection Kit, CinnaGen company, Iran). Results: Anti–CMV immunoglobulin (Ig) G antibodies were detected in GBS patients and healthy controls in 97% and 93% of children, respectively. Anti-CMV IgM antibodies were demonstrated in 33% (n=10) of the healthy controls and 33% (n=10) of the children with GBS. The borderline level of anti-CMV IgM antibodies was found in 23% healthy controls (n=7) and 13% (n=4) in the children with GBS (p=0.57), respectively. None of the specimens from the both controls the cases with GBS was positive for CMV DNA by PCR. Conclusion: These data demonstrated the presence of anti-CMV antibodies in a majority of both patients with GBS and controls and no relation between CMV infection and GBS was observed. However, further studies with larges sample sizes are highly recommended.